PENERAPAN METODE MAKE A MATCH UNTUK MENINGKATKAN KEMAMPUAN MENULIS PANTUN PADA SISWA KELAS VII SMP NEGERI 1 LAWE ALAS - Sa’adah Sa’adah; Irfan Johari (Tuwah Pande: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
This study aims to determine the improvement of rhyme writing skills through the application of the make a match method to class VII students of SMP Negeri 1 Lawe Alas in the 2021/2022 academic year. As for the population in this study were all students of class VII totaling 43 people and a sample of 22 people. The method used in this study is an experimental method with a one group pretest and posttest design with data analysis using the "t" test. From data processing, it was found that the average value of the initial test of rhyme writing skills by students was 62.27 and included in the less category, with a standard deviation of 4.29 and an increase in the final test score with an average value of 86.36 and included in the good category, with a standard deviation of 4.92. Based on the results of the students' initial and final test scores and if it is associated with the KKM value of Indonesian language subjects for junior high schools of 70, the students' rhyme writing skills are included in the good category. From hypothesis testing, it is obtained that the value of t count = 17.33 and in consultation with the value of t_table at a significant level of 5% = 2,080, thus t_count > t_table or 17.33 > 2,080 then the hypothesis is accepted. So it can be concluded that there is an increase in the ability to write rhymes through the make a match method in class VII students of SMP Negeri 1 Lawe Alas in the 2021/2022 academic year.